Pengaruh Model Pembelajaran Role Playing dalam Mengembangkan Kepercayaan Diri Siswa Kelas VI pada Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial - Pambudi, Ifnu Diky; Subhanadri, Subhanadri; Habibie, Zulqoidi R. (CV. Master Literasi Indonesia, 2025)
The topic of insufficient self-confidence among students in IPAS subjects served as the impetus for this thorough investigation. This study seeks to elucidate the role-playing learning paradigm's impact on sixth-grade students' self-confidence in IPAS topics at SDN 109/II Manggis. This study employed a quantitative research method and a quasi-experimental nonequivalent control group design, ensuring a comprehensive approach to the research. The research employed an experimental group, utilizing a sample from class VA. To evaluate the hypothesis in this study, the researcher employed non-parametric statistical tests, specifically the Wilcoxon test and the Mann-Whitney U test, utilizing SPSS version 26. The Wilcoxon and Mann-Whitney U test outcomes for the self-confidence variable indicated a significance of 0.000, less than 0.05, validating Ha. Similarly, the significance of the learning desire variable was also 0.000, confirming the acceptance of Ha. The hypothesis test results indicate that the self-confidence of grade VI students in IPAS topics utilizing the role-playing learning model significantly influences their self-confidence compared to those employing the conventional learning model